New species of many-plumed moths (Lepidoptera: Alucitidae) from Tanzania - Ustjuzhanin, Peter; Kovtunovich, Vasiliy; Ustjuzhanina, Anna (Zootaxa, 2018)
Basing on the examination of new material on many-plumed moths from Tanzania, four new species have been discovered: Alucita agassizi Ustjuzhanin & Kovtunovich sp. nov., A. iringiensis Ustjuzhanin & Kovtunovich sp. nov., A. snezhinka Ustjuzhanin & Kovtunovich sp. nov. and A. tanzanica Ustjuzhanin & Kovtunovich sp. nov. They are described and compared with the closest species. The diagnostic characters for each new taxon are specified. The genitalia are described and illustrated, images of the adults are provided. Data on many-plumed moths previously unknown for Tanzania are given. Two species, A. seychellensis (Fletcher 1910) and A. malawica (Ustjuzhanin & Kovtunovich, 2016) are reported from Tanzania for the first time.